Beyond Macroeconomics: the Dominant Role of Digital Acceleration in Driving BMT UGT Nusantara’s Growth - Faizatul Maghfirah; Anita Priantina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyzes the dynamic influence of digitalization and macroeconomic variables on the financial performance of BMT UGT Nusantara during 2020–2025 using a Vector Error Correction Model framework. The results confirm a long-run equilibrium relationship among digitalization, macroeconomic conditions, and BMT financial performance. Digitalization emerges as the dominant driver, where digital user adoption strongly drives intermediation efficiency while digital transaction volume generates the most persistent contribution to asset growth. Macroeconomic variables exert minimal direct causal influence, though inflation poses a more persistent threat to intermediation efficiency than interest rate movements. A fundamental asymmetry is identified in that breadth and depth of digitalization operate through distinct institutional channels. BMT management is encouraged to develop digitally accessible financing products to convert active transactors into productive financing participants. For regulators, this study provides empirical justification for policies facilitating digital transformation across Islamic microfinance cooperatives to strengthen financial inclusion and institutional resilience.